Population-based geographic variations in DXA bone density in Europe: the EVOS Study. European Vertebral Osteoporosis. - Lunt, M; Felsenberg, D; Adams, J; Benevolenskaya, L; Cannata, J; Dequeker, J; Dodenhof, C; Falch, J; Johnell, O; Khaw, K; Masaryk, P; Pols, H; et al. (1997)
The purpose of this study was to investigate variations in bone density between 16 European populations, 13 of which were participants in the European Vertebral Osteoporosis Study (EVOS). Men and women aged 50-80 years were recruited randomly from local population registers, stratified in 5-year age bands. The other three centres recruited similarly. Random samples of 20-100% of EVOS subjects were invited for dual-energy X-ray absorptiometry (DXA) densitometry of the lumbar spine and/or proximal femur using Hologic, Lunar or Norland pencil beam machines or, in one centre, a Sopha fan-beam machine. Cross-calibration of the different machines was undertaken using the European Spine Phantom prototype (ESPp). Highly significant differences in mean bone density were demonstrated between centres, giving rise to between centre SDs in bone density that were about a quarter of a population SD. These differences persisted when centres using Hologic machines and centres using Lunar machines were considered separately. The centres were ranked differently according to whether male or female subjects were being considered and according to site of measurement (L2-4, femoral neck or femoral trochanter). As expected, bone mineral density (BMD) had a curvilinear relationship with age, and apparent rates of decrease slowed as age advanced past 50 years in both sexes. In the spine, not only did male BMD usually appear to increase with age, but there was a highly significant difference between centres in the age effect in both sexes, suggesting a variability in the impact of osteoarthritis between centres. Weight was consistently positively associated with BMD, but the effects of height and armspan were less consistent. Logarithmic transformation was needed to normalize the regressions of BMD on the independent variates, and after transformation, all sites except the femoral neck in females showed significant increases in SD with age. Interestingly, the effect of increasing weight was to decrease dispersion in proximal femur measurements in both sexes, further accentuating the tendency in women for low body mass index to be associated with osteoporosis as defined by densitometry. It is concluded that there are major differences between BMD values in European population samples which, with variations in anthropometric variables, have the potential to contribute substantially to variations in rates of osteoporotic fracture risk in Europe.